Glycoprotein D-Independent Spread of Pseudorabies Virus Infection in Cultured Peripheral Nervous System Neurons in a Compartmented System - Ch'ng, T. H. (American Society for Microbiology, 2007)
The molecular mechanisms underlying the directional neuron-to-epithelial cell transport of herpesvirus particles during infection are poorly understood. To study the role of the viral glycoprotein D (gD) in the directional spread of herpes simplex virus (HSV) and pseudorabies virus (PRV) infection, a culture system consisting of sympathetic neurons or epithelial cells in different compartments was employed. We discovered that PRV infection could spread efficiently from neurons to cells and back to neurons in the absence of gD, the viral ligand required for entry of extracellular particles. Unexpectedly, PRV infection can also spread transneuronally via axo-axonal contacts. We show that this form of interaxonal spread between neurons is gD independent and is not mediated by extracellular virions. We also found that unlike PRV gD, HSV-1 gD is required for neuron-to-cell spread of infection. Neither of the host cell gD receptors (HVEM and nectin-1) is required in target primary fibroblasts for neuron-to-cell spread of HSV-1 or PRV infection.